FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM LAPORAN TAHUNAN PERUSAHAAN (Studi empiris terhadap perusahaan yang terdaftar pada bursa efek Indonesia) - Amsyari, Hafiz Akbar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study is a research conducted on companies listed on the Indonesia Stock Exchange. The purpose of this study was to determine the factors that affect the extensive disclosure of social responsibility (CSR) in the annual reports of companies in Indonesia. The research was based on previous studies that examined the amount of many CSR disclosure, and little research on the types of CSR was undertaken by the company. CSR is a business practice in which companies try to fulfill the desire of the shareholders and the public as well as in the hope of obtaining legitimacy from them. The factors used in this study include leverage, profitability, company size and size of the board of commissioners. Data collection methods used in this study was content analysis of the social disclosure in annual reports of companies. Content analysis was conducted using the check list items of social disclosure in annual reports of companies. This research was done to the company in Indonesia that listed in the Indonesia Stock Exchange 2010-2012. By using the final sample were 62 companies by using multiple regression. Results of this study indicate that size of the board of commissioners significantly affect the extensive disclosure of corporate social responsibility report, the other factors such as leverage, profitability, and firm size does not significantly affect the extensive disclosure of corporate social responsibility report. Keywords: corporate social responsibility (CSR), extensive disclosures, leverage, profitability, firm size, size of the board of commissioners